Evaluasi Kedisiplinan Kinerja Mentor Pendidikan Agama Kristen (PAK) pada Kegiatan Pusat Pengembangan Anak (PPA) IO 0164 Bethlehem Rote - Galang G.G Khuana (Damai : Jurnal Pendidikan Agama Kristen dan Filsafat, 2025)
Evaluation of PAK Performance Discipline in PPA IO 0164 Bethlehem Rote Activities. In this study, researchers found problems such as undisciplined performance in terms of time and responsibility as a mentor to mentor children at PPA IO 0164 Bethlehem Rote. Mentors who often arrive late for class. Mentors who are not responsible for teaching in class. There are even mentors who cannot be role models for children. The aim of this research is to reveal the causes of indiscipline in mentor performance and how to overcome it through the method that the researcher has prepared, namely a qualitative method with a research design, namely observation, interviews and literature study. Based on research findings, it is stated that there are still many mentors who do not carry out their responsibilities well. The most dominant reason for some mentors not being disciplined in their performance is that they have other work that interferes with their responsibilities as a mentor in PPA IO 0164 Bethlehem Rote activities. Apart from that, there are already disciplinary measures for mentors who are still undisciplined, but there are still mentors who still do it. The solution that researchers can provide is that a mentor must be able to understand that what he does as a mentor is a calling to be carried out because taking care of and even saving children through mentoring at PPA is a very significant responsibility.